Financial and governance factors toward tax avoidance with firm value and audit quality interaction / Vidiyanna Rizal Putri - Erizal, Vidiyanna Rizal Putri (2024)
Financial criminology in the form of tax avoidance practices has become a common issue in business entities in Indonesia. Legal profit maximization through exploiting tax loopholes is a common practice, reducing companies' tax obligations to the state. Although seemingly astute, it sparks ethical concerns and diminishes state revenues. Tax avoidance isn't exclusive to financial institutions, with various factors influencing its prevalence in the banking and non-bank financial sectors. Financial and governance factors play pivotal roles, while interventions in corporate value and high-quality audits, especially by reputable "big four" firms, empower companies to exploit tax loopholes confidently. The research aims to scrutinize these influences on tax avoidance in listed banks and non-bank financial institutions on the Indonesia Stock Exchange from 2015 to 2021.. There are only 61 banks and non-bank financial institutions that meet the criteria for the purposive sampling technique. In this context, previous research has yet to explore the influence of firm value and audit quality. Intervention against tax avoidance.